The Role of the Auditor in Confirming the Integrated Reports - An Exploratory Study on a Sample of External Auditors in Iraq- - AL-Saaedi, Reyam Farhan Zahraw; Al-Taie, Bushra Fadil (Journal of Economics and Administrative Sciences, 2022)
The aim of the research is to identify the extent of the ability to ensure the integrated reports by the auditor in verifying the credibility of these reports, and their implications for the benefit of all parties dealing with the economic unit, as well as measuring the impact of the assurance procedures followed by the auditors and their role in confirming these reports. The research methodology was designed after studying the previous literature related to the research variables, and then the relationship between these variables was tested, through the use of a questionnaire list. A questionnaire targeting the community of auditors in the local environment, and the results of the study were reached using the (SPSS) program and the application of statistical models to determine the correlation and influence between the variables. The most important conclusions shown by the study are that the process of confirming the integrated reports results in an evaluation of the information they contain by external auditors, who are usually qualified for such actions, are neutral and independent of the economic unit, and thus enable them to give a clear perception of the truthfulness of these reports’ representation of the information contained therein. Thus, reassuring all parties dealing with the economic unit and increasing their confidence in the content of the integrated reports. The most important recommendations made by the study are that professional organizations in Iraq must issue instructions or guiding rules regulating the process of confirming the integrated reports, and the Office of Financial Supervision, in cooperation with the Profession Council and the Audit of Accounts in Iraq, should qualify the auditors working in audit offices professionally and scientifically, to be able to complete the process of confirming the integrated reports in all its dimensions, as it creates a challenge for the profession of auditing